THE INFLUENCE OF INNOVATION, PROMOTION, AND COMPETITIVE ADVANTAGE ON CONSUMER LOYALTY MODERATED BY CONSUMER SATISFACTION AT PT FEDERAL INTERNATIONAL FINANCE - Citra Ayu Lestari; Imam Suryono; Lukiyana (RADJA PUBLIKA, 2026)
The financing industry in Indonesia is becoming increasingly competitive, requiring finance companies to strengthen customer loyalty through effective business strategies. This study aims to analyze the effects of innovation, promotion, and competitive advantage on consumer loyalty, with consumer satisfaction as a moderating variable at PT Federal International Finance (FIF). A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through questionnaires distributed to 171 consumers selected using purposive sampling. The findings indicate that promotion and consumer satisfaction have a positive and significant effect on consumer loyalty, whereas innovation and competitive advantage do not significantly influence loyalty. Furthermore, consumer satisfaction negatively moderates the relationship between innovation and consumer loyalty, positively moderates the relationship between competitive advantage and consumer loyalty, but does not moderate the relationship between promotion and consumer loyalty. The novelty of this study lies in integrating innovation, promotion, and competitive advantage simultaneously while positioning consumer satisfaction as a moderating variable to provide a more comprehensive understanding of consumer loyalty in the financing industry.